Optimizing the Radius of Curvature of Black Silicon Peaks for Solar Cell Using Matlab Simulations - Al-Rubaiee, Mohanad; Plaza, Guillermo Sanchez (Iraqi Journal of Science, 2021)
As part of our research on efficiency improvement of PERC (Passivated Emitter Rear Solar Cell), achieving very low reflectivity values of solar cell surface is a must. One of the most advance technologies to do so is the use of advanced texturing for the front surface of the cells. This texture, also known as Black Silicon, consists of peaks and valleys of nano metric dimensions and capable of dramatically reducing the reflectance of the front surface. A reflectance around 5% was reached ,using simulation, when using a Black-Silicon texturing with height of 50nm with peak rounding of 5nm. Even though this texturing may affect other parameters such as series resistance or surface recombination, as a starting point, simulation was used to find the optimum peak rounding, where the radius of curvature of the peak is maximum, while keeping reflectance as low as possible.